Innovación abierta: una revisión sistemática de la literatura - Portocarrero García, Milagros Sara (2023)
Open innovation is a new way of managing innovation. The purpose of this article is to explore and investigate the importance of open innovation, the understanding and evolution in the application by companies. A literature review was carried out in the Web of Science, Scopus and Proquest databases. This literature review process shows that open innovation is valuable for companies to use it. Apply, has an important place in innovation management, and can be applied not only by large companies, but also in small and medium-sized companies. Perspectives of the concept of Open Innovation from various authors are presented, and although the purpose is to use internal and external resources for the creation of new products, it is necessary to mention that innovation is essential for business growth and development.